The economic role of logistics quality assurance in the era of digitalisation - Nagy, Gábor (Advanced Logistic Systems - Theory and Practice, 2024)
Digitalisation has fundamentally transformed the logistics sector, elevating the importance of quality assurance as a cornerstone for operational efficiency, cost management, and customer satisfaction. As logistics processes become increasingly complex and data-driven, the role of quality assurance extends beyond traditional frameworks to embrace cutting-edge technologies such as artificial intelligence, blockchain, and the Internet of Things (IoT). This paper explores the economic implications of integrating these innovations into logistics quality assurance, focusing on their capacity to reduce operational costs, enhance supply chain transparency, and foster long-term customer loyalty. Through a detailed analysis, the study demonstrates how the convergence of digitalisation and quality assurance facilitates real-time monitoring, predictive analytics, and automation, resulting in significant competitive advantages. By adopting a hybrid approach that integrates traditional quality management principles with advanced digital tools, logistics companies can unlock unprecedented economic and strategic opportunities, positioning themselves as leaders in an increasingly global and digitised marketplace.